KONSEP HAK MILIK DALAM EKONOMI ISLAM - AN Ras Try Astuti; Andi Faisal (Muamalat: Jurnal Kajian Hukum Ekonomi Syariah, 2017)
Capitalism as an economic system that is implemented by most countries in the world today, in fact it gave birth to injustice and social inequalityare increasingly out of control. Social and economic inequalities are felt both between countries (developed and developing countries) as well as insociety itself (the rich minority and the poor majority). The condition is born from the practice of departing from faulty assumptions about the man. In capitalism the individual to own property released uncontrollably, causing a social imbalance. On the other hand, Islam never given a state model that guarantees fair distribution of ownership for all members of society, ie at the time of the Prophet Muhammad established the Islamic government in Medina. In Islam, the private ownership of property was also recognized but not absolute like capitalism. Islam also recognizes the forms of joint ownership for the benefit of society and acknowledges the ownership of the state that aims to create a balance and social justice.